Profesi Guru; Analisis Survei Masyarakat Jawa Barat Terhadap Minat Studi - Muhtar, Tatang; Lengkana, Anggi Setia; Alif, Muhammad Nur; Supriyadi, Tedi (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2022)
This study aimed to analyze the extent of interest in further studies of high school/vocational/MA grade 3 students in West Java Province. The method used is quantitative with a survey design. The number of samples in this study was 330 people with the sampling technique using Accidental Sampling. The instrument is a questionnaire distributed to respondents, then processed using Microsoft Excel and presented in a diagram. This study concludes that public interest in the Physical Education and Recreational Health (PJKR) study program is extensive. This can be the basis for consideration for policymakers in formulating the PJKR study program as part of efforts to facilitate community needs in the field of physical education.